Anomalous Diffusion by Ocean Waves and Eddies - Joey J. Voermans; Alexander V. Babanin; Alexei T. Skvortsov; Cagil Kirezci; Muhannad W. Gamaleldin; Henrique Rapizo; Luciano P. Pezzi; Marcelo F. Santini; Petra Heil (Journal of Marine Science and Engineering, 2024)
Understanding the dispersion of floating objects and ocean properties at the ocean surface is crucial for various applications, including oil spill management, debris tracking and search and rescue operations. While mesoscale turbulence has been recognized as a primary driver of dispersion, the role of submesoscale processes is poorly understood. This study investigates the largely unexplored mechanism of dispersion by refracted wave fields. In situ observations demonstrate significantly faster and distinct dispersion patterns for objects influenced by wind, waves and currents compared to those solely driven by ocean currents. Numerical simulations of wave fields refracted by ocean eddies corroborate these findings, revealing diffusivities that exceed those of turbulent diffusion at scales up to 10 km during energetic sea states. Our results highlight the importance of ocean waves in dispersing surface material, suggesting that refracted wave fields may play a significant role in submesoscale spreading. As atmospheric forcing at the ocean surface will only strengthen due to anthropogenic contributions, additional research into wave refraction is necessary. This requires concurrent high-resolution measurements of wind, waves and currents to inform the revisions of large-scale coupled models to better include the submesoscale physics.

A simple method for calculating the probability of quiescent periods in random seas for maritime search and rescue operations - Sasan Tavakoli; Cagil Kirezci; Junghoon Lee; Daniel Sgarioto; Alexei T. Skvortsov; Alexander V. Babanin (Ocean Engineering, 2024)